Lacosamide monotherapy in clinical practice: A retrospective chart review. (14th March 2018) - Villanueva, V.; Giráldez, B. G.; Toledo, M.; De Haan, G. J.; Cumbo, E.; Gambardella, A.; De Backer, M.; Joeres, L.; Brunnert, M.; Dedeken, P.; Serratosa, J.
Abstract : Objective: To assess effectiveness and tolerability of first‐line and conversion to lacosamide monotherapy for focal seizures. Materials and Methods: Retrospective, non‐interventional chart review of lacosamide monotherapy patients aged ≥16 years in Europe. Outcomes included retention rate at observational point (OP) 3 (12 ± 3 months), seizure freedom rates at OP2 (6 ± 3 months) and OP3 and adverse drug reactions (ADRs). Results: A total of 439 patients were included (98 first‐line and 341 conversion to monotherapy; 128 aged ≥65 years [25 first‐line and 103 conversion to monotherapy]). First‐line and conversion to monotherapy retention rates were 60.2% (59/98; 95% confidence interval [CI] 49.8%‐70.0%) and 62.5% (213/341; 57.1%‐67.6%), respectively. Kaplan‐Meier estimates of 12‐month retention rates were 81.2% and 91.4% for first‐line and conversion to monotherapy, respectively. First‐line and conversion to monotherapy retention rates in patients aged ≥65 years were 60.0% (38.7%‐78.9%) and 68.9% (59.1%‐77.7%), respectively. At OP2, 66.3% of first‐line and 63.0% of conversion to monotherapy patients were seizure free. At OP3, 60.2% of first‐line and 52.5% of conversion to monotherapy patients were seizure free. In the ≥65 years subgroup, seizure freedom rates at OP2 were 72.0% and 68.0% for first‐line and converted to monotherapy, respectively, and at OP3, 68.0% and 56.3%, respectively. Overall, 52 of 439 (11.8%) patients reported ADRs (16.4% in ≥65 years subgroup), most commonly dizziness (5.0%), headache (2.1%) and somnolence (1.6%). Conclusions: Lacosamide was effective and well tolerated as first‐line or conversion to monotherapy in a clinical setting in adult and elderly patients with focal seizures.